2011
DOI: 10.5194/angeo-29-209-2011
|View full text |Cite
|
Sign up to set email alerts
|

Case study of a mesospheric wall event over Ferraz station, Antarctica (62° S)

Abstract: On 16–17 July 2007 during an observational campaign at Comandante Ferraz Antarctic Station (62° S, 58° W), a mesospheric wall was observed with an airglow all-sky imager. The wave appeared like an extensive dark region in the all-sky airglow images, with a large depletion in the OH emission. Simultaneous mesospheric winds measured with a MF radar at Rothera station and temperature profiles from SABER instrument, on board of TIMED satellite, were used to obtain the propagation condition of the wave. Wind measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 28 publications
5
28
0
Order By: Relevance
“…The report of only two wave front events (wall event reported by Bageston et al (2011) and the present study), among a large number of gravity wave events, confirms the low occurrence rate of bores at high southern latitudes compared to lower latitudes (Fechine et al, , 2009). The event reported here could not be classified as a mesospheric bore according to the criteria used in the literature (Dewan and Picard, 1998;Smith et al, 2003;Brown et al, 2004;Smith et al, 2005).…”
Section: Introductionsupporting
confidence: 50%
See 3 more Smart Citations
“…The report of only two wave front events (wall event reported by Bageston et al (2011) and the present study), among a large number of gravity wave events, confirms the low occurrence rate of bores at high southern latitudes compared to lower latitudes (Fechine et al, , 2009). The event reported here could not be classified as a mesospheric bore according to the criteria used in the literature (Dewan and Picard, 1998;Smith et al, 2003;Brown et al, 2004;Smith et al, 2005).…”
Section: Introductionsupporting
confidence: 50%
“…2b). Indeed, temperature inversions, or thermal ducts, have often been associated with mesospheric fronts Picard, 1998, 2001;Smith et al, 2003;She et al, 2004;Smith et al, 2005;Narayanan et al, 2009;Laughman et al, 2009Laughman et al, , 2011Bageston et al, 2011). The intrinsic phase speed along the direction of propagation implied by the estimated m 2 profile is from ∼50 to 70 m s −1 , depending on whether we take the relevant background wind to be the maximum in the direction of propagation or that centered in the ducting region (with m 2 > 0).…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bageston et al (2009) in their observations at Ferraz Station, during 2007, observed more than 230 gravity wave events, but only two clear cases of mesospheric fronts were reported. The first one was a mesospheric wall (Bageston et al, 2011a) and the second one was a mesospheric bore (Bageston et al, 2011b). In both cases, the fronts were supported by stable ducts (the first one a thermal duct and the second one a thermal-Doppler duct).…”
mentioning
confidence: 96%